THE ART OF DESIGNING AN INFORMATICS COURSE: HOW TO CREATE THE PERFECT LEARNING SPACE FOR STUDENTS? - Jancheski, Metodija; Jancheska, Sofija (IATED, 2023)
Designing an informatics course has become a great challenge. The rapid technological developments coupled with today’s abundance of online learning materials have made it tricky for educators to design effective class curriculums. Our paper will provide educators with the winning formula for students’ perfect learning experience. We aim to inspire educators to leverage modern tools to create engaging and fruitful classes. Our work is a general toolbox which will enable educators to tailor their classes to different areas within the field of informatics. We thus aim to answer the following questions: “How to prepare well for an informatics class?”, “How to conduct an informatics class successfully?” and “How to evaluate a properly conducted informatics lesson?”. Our paper will familiarize educators with the whole cycle of designing a successful informatics course. We will specifically target the microlevels of a course, a lesson. We will discuss different aspects of every lesson: suitable methods for organization and planning of a lesson, structural elements of a lesson, types of lessons, didactic goals, appropriate selection of teaching material, active methods for teaching and learning, manners for fostering interaction between students and teachers and among students themselves, approaches to fully engage students, lesson delivery models, individualized techniques to target the learning goals of each student, assessment and evaluation of students. We will also take into consideration teachers’ preparedness including their expertise of the material, and their didactical, technical and psychological readiness. The quality of an informatics course lies in the relationship between educators and their students. It is a complex dynamic between teachers’ goals, plans, means, methods and organization, and students’ expectations, abilities, and motivation. Our paper reaches an equilibrium point between all the building blocks of the teaching process of the educator and learning experience of the students. Our focus is put on the teacher and their teaching methods and tactics. We perceive the teachers as pilots leading a full airplane, a class of students. They have a palette of gadgets available, and they need to make a specific choice for the plane to conformably fly and to finally land on the exact coordinates of the intended location. In our case, the fancy gadgets are all traditional and modern learning tools available to the teacher and the intended location is the goal of the teacher for the class. How can educators use the tools to meet their didactic goals? When should they use them at what times? What specific tools should they select for special educational tasks? What does this choice depend on? Our paper will take a holistic view of all components of the process of teaching and learning informatics.
Keywords: Informatics; teaching and learning; course; lesson; active methods